Friday

September 19, 2014

September 19, 2014

Posted by **Fatima** on Sunday, September 23, 2012 at 3:14am.

- precalculus -
**Steve**, Sunday, September 23, 2012 at 8:10amsince f(x) is even, f(-z) = f(z)

g(-x) = -g(x) since g is odd

f(g(-x)) = f(-g(x)) = f(g(x)) so fog is even

**Answer this Question**

**Related Questions**

precalculus - Suppose g is an even function and f is any function such that the ...

algebra - Give am example of a function f.N N with the property that there ...

Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Give a brief ...

Calculus, check my answers, please! 3 - Did I get these practice questions right...

odd and even functions - Using f is odd if f(-x) = -f(x) or even if f(-x) = f(x...

precalculus - Precalculus-------Give an example of three functions f,g,h none of...

math - I know It's probably an easy question but I don't know remember how to do...

Algebra - Confused Please Help! Thanks! Let f(x) = 1 – 3x^2. Which of the ...

Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Please give us a ...

Algebra - Let f(x) = 1 – 3x^2. Which of the following is true? Give a brief ...